Pest risk assessment of Radopholus similis for the EU territory. (23rd August 2017) - ,; Jeger, Michael; Bragard, Claude; Caffier, David; Candresse, Thierry; Chatzivassiliou, Elisavet; Dehnen‐Schmutz, Katharina; Gilioli, Gianni; Grégoire, Jean‐Claude; Jaques Miret, Josep Anton; MacLeod, Alan; Navajas Navarro, Maria; et al.
Abstract: The Panel on Plant Health performed a pest risk assessment on Radopholus similis, the burrowing nematode for the EU. The quantitative assessment focused on entry, establishment, spread and impact on tropical and subtropical ornamental host plants, the main pathways for entry of R. similis into the EU. Infested consignments are expected to enter the risk assessment area on ornamentals under all scenarios. For citrus, which is a closed pathway for entry, outdoor establishment was assessed. Establishment may only take place after successful transfer from ornamental plants to citrus production systems. This event is called 'shift' in this assessment, to indicate that this is an unusual transfer. It has been estimated that establishment of this nematode in the open field in the EU citrus production areas under current temperatures is possible in most parts of the citrus production area in the EU. Temperature conditions will prevent the nematode from establishing only in the northernmost citrus areas and at higher altitudes in the south. Host plants for planting originating from infested places of production (greenhouses) within the risk assessment area are considered the main pathway for spread within the risk assessment area. Under current climatic conditions, the population of R. similis is not expected to reach damaging population levels in the open field. In case of increased temperatures due to global warming, the nematode population may reach damaging levels in very few places outdoors. Currently, main impact is considered for ornamental greenhouse production in the risk assessment area. Impact will be either caused by direct plant growth reductions or loss due to phytosanitary measures applied on regulated plants. Despite the fact that R. similis is globally considered as one of the most destructive plant parasitic nematodes, the impact in the risk assessment area is considered low.